Cooperative Method of Talking Chips Types in Character Education to Improve Discipline of SMP Students - Novilia Mita Sari (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
The purpose of this study is to determine the cooperative method of talking chips type in character education for junior high school students. Data is taken from trusted literature such as books and journals. The method used is a match (looking for a partner), 2. Think Fair-Share (thinking-pairing), 3. Talking chips, 4. roundtable. The results will be expected later for junior high school students when the learning process and student learning are more active, disciplined, organized and evenly distributed. Keywords: method, students, character education, discipline